Different worlds of contention? Protest in Northwestern, Southern and Eastern Europe - Endre Borbáth; Theresa Gessler (European Journal of Political Research, 2020)
Despite the voluminous literature on the `normalisation of protest', the protest arena is seen as a bastion of left-wing mobilisation. While citizens on the left readily turn to the streets, citizens on the right only settle for it as a `second best option'. However, most studies are based on aggregated cross-national comparisons or only include Northwestern Europe. We contend the aggregate-level perspective hides different dynamics of protest across Europe. Based on individual-level data from the European Social Survey (2002–2016), we investigate the relationship between ideology and protest as a key component of the normalisation of protest. Using hierarchical logistic regression models, we show that while protest is becoming more common, citizens with different ideological views are not equal in their protest participation across the three European regions. Instead of a general left predominance, we find that in Eastern European countries, right-wing citizens are more likely to protest than those on the left. In Northwestern and Southern European countries, we find the reverse relationship, left-wing citizens are more likely to protest than their right-wing counterparts. Lessons drawn from the protest experience in Northwestern Europe characterised by historical mobilisation by the New Left are of limited use for explaining the ideological composition of protest in the Southern and Eastern European countries. We identify historical and contemporary regime access as the mechanism underlying regional patterns: citizens with ideological views that were historically in opposition are more likely to protest. In terms of contemporary regime access, we find that partisanship enhances the effect of ideology, while ideological distance from the government has a different effect in the three regions. As protest gains in importance as a form of participation, the paper contributes to our understanding of regional divergence in the extent to which citizens with varying ideological views use this tool.
https://doi.org/10.7910/DVN/HUEPQJ
Keywords: 330; protest; left-right ideology; historical legacies; contentious politics; political participation